DIRECT SYNTHESIS OF BIS(SILYL)METHANES CONTAINING SI-H BONDS - JUNG, IN; YEON, SH; HAN, JS (AMER CHEMICAL SOC, 1993)
A series of Si-H-containing bis(silyl)methanes has been prepared by reacting directly elemental silicon simultaneously with (chloromethyl)silanes and hydrogen chloride in the presence of a coppercatalyst using a stirred reactor equipped with a spiral band agitator at carefully controlled temperatures between 280 and 340-degrees-C. Bis(silyl)methanes containing dichlorosilyl groups were obtained as the major products and trichlorosilyl-group-containing bis(silyl)methanes as minor products. Cadmium was a good promoter for the reaction, while zinc was found to be an inhibitor.